Parental behavior and newborn attachment in birds: life history traits and endocrine responses - Mota-Rojas, Daniel; Marcet-Rius, Míriam; Domínguez-Oliva, Adriana; Buenhombre, Jhon; Daza-Cardona, Erika Alexandra; Lezama-García, Karina; Olmos-Hernández, Adriana; Verduzco-Mendoza, Antonio; Bienboire-Frosini, Cécile (Frontiers in Psychology, 2023)
In birds, parental care and attachment period differ widely depending on the species (altricial or precocial), developmental strategies, and life history traits. In most bird species, parental care can be provided by both female and male individuals and includes specific stages such as nesting, laying, and hatching. During said periods, a series of neuroendocrine responses are triggered to motivate parental care and attachment. These behaviors are vital for offspring survival, development, social bonding, intergenerational learning, reproductive success, and ultimately, the overall fitness and evolution of bird populations in a variety of environments. Thus, this review aims to describe and analyze the behavioral and endocrine systems of parental care and newborn attachment in birds during each stage of the post-hatching period.